Integrative islamic personality inventory: development and validation - Ismail, Nik Ahmad Hisham; Teke, Mustafa (IIUM Press, 2015)
With the growing awareness of the need to integrate modern psychological approaches with Islamic values and practices, there is a need among Muslim psychologists and other behavioral scientists for an instrument capable of capturing the major elements of the Islamic personality. Therefore, the purpose of this study was to develop and take the first steps in the validation of the Integrative Islamic Personality Inventory (IIPI), which is a newly developed measurement. With regard to content validity, 64 items were generated based on the judgments of a panel of experts. Fifty-seven respondents completed the preliminary instrument. The inventory demonstrated excellent reliability and strong internal validity. In the next phases, the inventory will be further validated and calibrated based on different psychometric standards and models